Innate immune reprogramming in circulating neutrophils of COPD patients - Mariotti, Barbara; Bracaglia, Chiara; Gasperini, Sara; Sartori, Giulia; Crisafulli, Ernesto; Bazzoni, Flavia (Journal of allergy and clinical immunology, 2025)
Chronic obstructive pulmonary disease (COPD) involves both local and systemic neutrophilic inflammation, with dysregulation in blood neutrophil numbers, frequencies, and functions. We sought to characterize the transcriptional and epigenetic profiles of circulating neutrophils in patients with COPD and explore correlations with neutrophil dysfunction and clinical disease parameters. Circulating neutrophils of patients with COPD and control donors were subjected to RNA-sequencing and genome-wide analysis of histone 3 lysine 4 trimethylation (H3K4me3) by chromatin immunoprecipitation coupled with sequencing. Neutrophils’ activation was assessed by cytofluorimetric analysis, O2− release, and Candida albicans phagocytosis assays. RNA- and chromatin immunoprecipitation–sequencing analysis of H3K4me3 revealed a poised state in genes involved in innate immune activation, resembling the phenotype observed in neutrophils from individuals who are BCG-vaccinated, referred to as “trained,” that is marked by weak or no expression under resting conditions but ready to be expressed at higher levels on stimulation. The epigenetic signature identified in neutrophils from subjects who are BCG-vaccinated was enriched in COPD neutrophils. In particular, and consistent with what has been described in “trained” neutrophils, COPD neutrophils exhibited transcriptional reprogramming of metabolically relevant genes. Functionally, COPD neutrophils produced higher CXCL8 and IL1B levels, released more O2−, and displayed greater phagocytic activity on in vitro stimulation. These findings suggest that COPD neutrophils undergo epigenetic, transcriptomic, and metabolic reprogramming, which enhances their responsiveness and aligns with the phenotype of neutrophils previously identified as trained, offering mechanistic insight into the functional dysregulation observed in COPD.